2000
DOI: 10.3168/jds.s0022-0302(00)74863-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yeast Culture (Saccharomyces cerevisiae) on Prepartum Intake and Postpartum Intake and Milk Production of Jersey Cows

Abstract: Yeast cultures (Saccharomyces cerevisiae; YC) have been added to diets for dry and lactating dairy cows to attempt to improve ruminal fermentation, potentially increasing dry matter intake (DMI) and milk yield. Jersey cows (14 primigravid and 25 multigravid) were fed total mixed rations prepartum and postpartum that were either supplemented or not supplemented with YC. The YC was a dried product that was top-dressed at 60 g/d for approximately 21 d prepartum and 140 d postpartum. The DMI was increased by YC du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
121
2
12

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(164 citation statements)
references
References 13 publications
29
121
2
12
Order By: Relevance
“…So, while Hadjipanayiotou et al [13] reported no effects on intake, BW, milk yield or milk composition, Giger-Reverdin et al [11] observed a significant increase in fat corrected milk yield and fat content in dairy goats. Similar contradictory results in yeast supplementation were observed in dairy cows as a consequence of the differences in various factors such as the type of forage fed, feeding strategy, forage to concentrate ratio and stage of lactation [9,20,23,25].…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…So, while Hadjipanayiotou et al [13] reported no effects on intake, BW, milk yield or milk composition, Giger-Reverdin et al [11] observed a significant increase in fat corrected milk yield and fat content in dairy goats. Similar contradictory results in yeast supplementation were observed in dairy cows as a consequence of the differences in various factors such as the type of forage fed, feeding strategy, forage to concentrate ratio and stage of lactation [9,20,23,25].…”
Section: Resultsmentioning
confidence: 60%
“…However, the results on the use of S. cerevisiae in dairy cows [9,20,23] and dairy goats [11,13] are also contradictory. Dietary factors such as forage concentrate ratio and forage type are important in determining the response to malate and yeast culture supplementation [20], which may explain the contradiction found in the results of the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Brewer's yeast or live yeast has been considered as possible candidates. Yeast has been typically included in calf diets at levels between 0.001% and 1.00%, with some positive effects on DMI, rumen pH and nutrient digestibility (Wagner et al, 1990;Quigley et al, 1992;Callaway and Martin, 1997;Kumar et al, 1997;Dann et al, 2000). Previous studies have explained the beneficial effects of yeast products as due to yeast cell components and fermented products such as organic acids, vitamins and nucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of Saccharomyces cerevisiae reduced CH 4 by 10% in vitro, but was not sustained over a long period (Mutsvangwa et al 1992). It has been shown that yeast culture influenced microbial metabolism and improved DMI, fiber digestion, and milk production in lactating cattle (Shaver and Garrett 1995;Doreau and Jouany 1998;Dann et al 2000). However, the specific mode of action is still unknown.…”
Section: New Potential Mitigation Options Probioticsmentioning
confidence: 99%